On exploring the Zaporozhian Sich’s kurins: origins of names, their timeline, and historical topography (encyclopedic aspects) - Anatoly Avramenko (Енциклопедичний Вісник України, 2023)
The study is dedicated to the issue of information reliability in encyclopedias. The author, who recently published a monograph on the names of Zaporozhian Sich’s settlements [kurins] (this article serves as a reflection on it), illustrates how information from scientific sources, already disproven and considered unfounded, incorrect, and distorting numerous historical facts of Ukraine, often finds its way into the pages of encyclopedias, textbooks, and other literature intended for a broad readership. Using the analysis of specific historical facts related to the Zaporozhian Sich, particularly the names of its settlements, author demonstrates the kind of information that should replace mythical content in reference and educational literature, disseminating more accurate knowledge in society.